Residual Effect of Integrated Nutrient Management on Growth, Yield and Quality of Vegetable Clusterbean - Chhipa, B G; Chandra, Atul; Gulati, I J (Annals of Arid Zone, 2018)
A field experiment was conducted at Horticulture Farm, College of Agriculture, Bikaner (Rajasthan) to evaluate the residual effect of organic and inorganic sources of nutrients on growth, yield and quality of vegetable clusterbean var. Pusa Navbhar. The results showed that among different growth parameters viz. average plant height (17.41 cm) was maximum under vermicompost. Among different levels of organic manures, 21 t ha-1 recorded maximum plant height (20.17 cm). Among different fertilizer doses, application of 100% recommended doses (RD) recorded maximum average plant height (17.26 cm). Similarly with respect to yield attributing parameters, average pod length (8.40 cm), pod yield (41.03 q ha-1) were maximum under vermicompost. Among different levels of organic manures, 21 t ha-1 produced maximum average pod length (8.78 cm), average pod weight (8.99 g), pod yield (42.21 q ha-1). Among different fertilizer doses, maximum average pod length (8.17 cm), average pod weight (7.94 g), pod yield (41.43 q ha-1) were recorded under the treatment of 100% RD. Quality parameters viz. nitrogen in pod (1.94%), protein (12.12%) and fibre (9.61%), iron (87.86 ppm), copper (6.81 ppm) and zinc (32.68 ppm) were maximum under vermicompost and phosphorous content was maximum (0.29%) under PROM. However, potassium content showed non-significant differences with respect to different sources of organic manures. Among its various levels, treatment consisting of 21 t ha-1 recorded highest nitrogen (1.96%), phosphorous (0.28%), potassium (0.21%), iron (88.71 ppm), copper (6.82 ppm) and zinc (32.45 ppm) in pods of clusterbean. Key words: Clusterbean, organic sources, integrated nutrient management, residual effect, FYM, PROM.